2000
DOI: 10.1111/j.1346-8138.2000.tb02122.x
|View full text |Cite
|
Sign up to set email alerts
|

Melasma in Men: A Hormonal Profile

Abstract: Melasma in men is much less common than in women. In the present communication, we evaluated circulating levels of LH, FSH, and testosterone in 15 men with idiopathic melasma. When compared with eleven age matched control men, the circulating LH was significantly higher and testosterone was markedly low in the melasmic men. We conclude that male melasma involves subtle testicular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 4 publications
4
27
0
2
Order By: Relevance
“…74 Furthermore, increased levels of LH and reduced levels of testosterone were identified in 15 men with melasma in India. 75 In France, it was reported the case of a man with complete hypogonadism - which increases LH and FSH levels, and reduces testosterone levels - who developed facial melasma. 76 …”
Section: Etiology Physiopathology and Risk Factorsmentioning
confidence: 99%
“…74 Furthermore, increased levels of LH and reduced levels of testosterone were identified in 15 men with melasma in India. 75 In France, it was reported the case of a man with complete hypogonadism - which increases LH and FSH levels, and reduces testosterone levels - who developed facial melasma. 76 …”
Section: Etiology Physiopathology and Risk Factorsmentioning
confidence: 99%
“…[8] Other etiological factors that have been described in men with melasma include the use of vegetable oil especially mustard oil on the face[57] and diethylstilboestrol therapy for prostate cancer. [8]…”
Section: Epidemiologymentioning
confidence: 99%
“…On the other hand, previous studies have suggested that the main associated factors of melasma in men are: UV irradiation, genetic influences, and subtle testicular resistance. [2][3][4]9 Knowledge of the morphologic and histopathological characteristics of melasma in men is essential to understand its pathogenesis. The aim of the current study was to investigate the histopathological differences between male melasma skin and the adjacent control skin, and to compare the histopathological characteristics of male melasma skin with those of female melasma and nonmelasma skin with solar lentigo.…”
mentioning
confidence: 99%